An introduction to Malay manuscripts - Wan Mamat, Wan Ali (IIUM Press, 2014)
Malay manuscripts are basically records of intellectual and cultural development, transmission and achievement of Malay civilization over generations. Old handwritten texts by Malay literati's in the olden days are known as manuscripts. It covers various subjects and is a very valuable reading source in understanding Malay thinking and civilization. Reviews on Malay manuscripts contents are fairly obtainable in the form of books, journals and conference proceedings but it does not cover the aspect of Malay traditional book making. Reading Malay manuscripts alone is not sufficient to make us understand Malay thinking and civilization. It should be supplement with informations on the various physical aspects that makes a Malay manuscript or book possible. This book is written in order to fill that gap. Thus the main objective of this book is to document Malay bookmaking tradition.